Spatial Pattern of Multi-dimensional Regional Disparities in the Level of Socio-economic Development in West Bengal: A Geographical Analysis - Suranjan Majumder (Department of Geography Education, University of Jember, 2021)
Micro-level spatial analysis of the different phenomenon duly associated with human development and also with the wellbeing of a nation. The study is a heart-core attempt to examine the inter-block regional disparity and development by constructing a multi-dimensional approach-based index. The study used thirty-four sub-dimensional variables under the five dimensions, including health, education, economy, socio-demography, and transport. The article used the data of the district statistical handbook of 2013 and census data of 2011. The empirical results of the study confirm the existence of huge inter-regional disparity on multi-dimensional developmental aspects, which drastically hampers the all-round growth and socio-economic development of Jalpaiguri Administrative Dvision (JAD) of West Bengal. The blocks of Khairabari, Darjeeling-Pulbazar, Rngli-rangit, Mirik, Kurseong, Kalimpong I & II are found to be high regional imbalances in the development of education, health, employment, and economy. The study also helps to identify the most backward blocks. It confirms the huge inter-block/district disparities in West Bengal. The study argued that the low developed and high disparities blocks require special attention from policymakers in order to the improvement of overall socio-economic development of the study area. Keywords: Jalpaiguri Administrative Dvision; Multi-dimensonal approach; regional disparity; regional imbalances; socio-economic development Copyright (c) 2021 Geosfera Indonesia and Department of Geography Education, University of Jember This work is licensed under a Creative Commons Attribution-Share A like 4.0 International License